1999
DOI: 10.1074/jbc.274.21.14850
|View full text |Cite
|
Sign up to set email alerts
|

Peroxygenase Metabolism of N-Acetylbenzidine by Prostaglandin H Synthase

Abstract: Synthesis of prostaglandin H 2 by prostaglandin H synthase (PHS) results in a two Prostaglandin H synthase (PHS)1 catalyzes the metabolism of arachidonic acid in the presence of molecular oxygen to form prostaglandin (PG) H 2 (1). PGH 2 is the common substrate utilized to synthesize a family of biologically important compounds referred to as prostanoids. There are two PHS isozymes, COX-1 and COX-2, which are encoded by two different genes (2, 3). COX-1 is the constitutive enzyme, whereas COX-2 is inducible. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Studies have shown that the metabolic activation of primary and tertiary aromatic amines by prostaglandin H synthase does not involve the N-hydroxy intermediate step [44]. Studies on aromatic amines such as Nacetylbenzidine (ABZ) have shown that they can be metabolized through alternate pathways by peroxygenase to produce DNA adducts [45]. Comparison of the derived adduct with synthetic standards by HPLC confirmed the formation of dGp-ABZ by this mechanism [46].…”
Section: Discussionmentioning
confidence: 85%
“…Studies have shown that the metabolic activation of primary and tertiary aromatic amines by prostaglandin H synthase does not involve the N-hydroxy intermediate step [44]. Studies on aromatic amines such as Nacetylbenzidine (ABZ) have shown that they can be metabolized through alternate pathways by peroxygenase to produce DNA adducts [45]. Comparison of the derived adduct with synthetic standards by HPLC confirmed the formation of dGp-ABZ by this mechanism [46].…”
Section: Discussionmentioning
confidence: 85%
“…Peroxidative activation of carcinogenic aromatic amines via prostaglandin H synthase has been reported (27,28). Recombinant human COX-1 and COX-2 enzymes have been shown to activate aromatic and heterocyclic amine carcinogens to intracellular electrophiles that bind covalently to DNA (29).…”
Section: Discussionmentioning
confidence: 99%
“…Recognition of Zenser's ability to detect N 0 -hydroxy-N-acetylbenzidine on incubation with N-acetylbenzidine and PHS is not convincing that it would actually influence DNA modification in the urothelium. 5 If this were to be the case, one could argue that activation by PHS would be important for simple aromatic monoamines such as 2-aminofluorene and 2-aminonaphthalene.…”
Section: Dear Sirmentioning
confidence: 99%
“…5 If this were to be the case, one could argue that activation by PHS would be important for simple aromatic monoamines such as 2-aminofluorene and 2-aminonaphthalene.…”
Section: Dear Sirmentioning
confidence: 99%